2021
DOI: 10.1007/s10143-021-01603-4
|View full text |Cite
|
Sign up to set email alerts
|

Microsurgical treatment of symptomatic vestibular schwannomas in patients under 40: different results before and after age of 30

Abstract: Background: In 10-15% of cases of vestibular schwannoma (VS) age at diagnosis is 40 years or less.Little is known about the differences in natural history, surgical ndings and postoperative outcomes of such younger patients as compared to those of greater age. Objectives : To analyze clinical and surgical and imaging data of a consecutive series of n=50 patients with unilateral sporadic VS, aged 40 years or younger -separated in a very young group (15-30 years) and a moderately young group (31-40 years). Study… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Luciano et al. found that in younger patients, tumor adhesions were more common and tended to be larger in size, abundant in blood supply, and excessive intraoperative bleeding ( 21 ). This suggests that vestibular schwannomas in young patients seem to have special characteristics, which should be paid attention to during the treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Luciano et al. found that in younger patients, tumor adhesions were more common and tended to be larger in size, abundant in blood supply, and excessive intraoperative bleeding ( 21 ). This suggests that vestibular schwannomas in young patients seem to have special characteristics, which should be paid attention to during the treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective cohort study of 596 patients conducted by Nick et al, the risk of tumor recurrence was significantly higher in younger patients than in older patients and suggested that this may be due to some host-related factor that promotes tumor growth (7). Luciano et al found that in younger patients, tumor adhesions were more common and tended to be larger in size, abundant in blood supply, and excessive intraoperative bleeding (21). This suggests that vestibular schwannomas in young patients seem to have special characteristics, which should be paid attention to during the treatment.…”
Section: Discussionmentioning
confidence: 99%